Abiotic subsurface behaviors of As(V) with Fe(II) - Lee, Sang-Hun; Jung, Woosik; Jeon, Byong-Hun; Choi, Jae-Young; Kim, Sunjoon (SPRINGER, 2011)
Subsurface geochemical behavior of As(V) with Fe(II) was studied under strict anoxic conditions. Abiotic reduction of As(V) (0.1 mM) to As(III) by aqueous Fe(II) and sorbed Fe(II) in pH range 5.0-7.0 and Fe(II)(aq) concentration (0.6-1.2 mM) was investigated along with the effect of As(V) on the oxidation of Fe(II) by dissolved oxygen (DO). Although the reduction was thermodynamically feasible for homogeneous chemical conditions, practically no As(V) reduction by aqueous Fe(II) was observed. Similarly, no sorbed As(V) reduction was observed under the heterogeneous experimental conditions by sorbed Fe(II) onto synthetic iron oxide (hematite, alpha-Fe2O3). Experimental results on Fe(II) oxidation by DO in the presence of 0.1 mM As(V) showed a significantly slower Fe(II) oxidation, which might be due to the formation of Fe(II)-As(V) complex in the aqueous phase. The results of this study demonstrate that As(V) is relatively stable in the presence of Fe(II) under subsurface environment and interfere the oxidation of Fe(II).
Keywords: ARSENIC CONTAMINATION; DRINKING-WATER; REDUCTION; GROUNDWATER; IRON; OXIDATION; SOLUBILITY; SPECIATION; KINETICS; REMOVAL